A case of thymoma-associated multiorgan autoimmunity including polymyositis and myocarditis - Chihiro Furuta; Motoki Yano; Hiroki Numanami; Masayuki Yamaji; Rumiko Taguchi; Masayuki Haniuda (Surgical Case Reports)
Abstract Background Polymyositis and myocarditis associated with thymoma are exceptionally rare conditions and usually accompanied by myasthenia gravis (MG) and have been recognized as critical conditions. Thymoma-associated multiorgan autoimmunity was reported recently with skin, liver, and intestinal manifestations similar to those seen in graft-versus-host disease. Case presentation A 77-year-old female presented to our department with exacerbation of ptosis and local recurrence of thymoma. Chest computed tomography revealed local recurrence of thymoma. Following 6 month observation, erythema on the extremities and body trunk suddenly appeared. Afterwards, the patient developed progressive muscle weakness and fatigue. We diagnosed as myocarditis and polymyositis. She was transferred to the intensive-care unit and received artificial ventilation. Steroid pulse therapy was induced immediately. The blood test findings were markedly improved, but the symptoms of MG and weakness of the muscles persisted. Various treatment including eculizumab was induced, and the symptoms of MG and weakness of the muscles were improved. On the 136th day of hospitalization, she was discharged. Conclusion We were able to cure this patient, as we were able to start treatment immediately after the appearance of severe symptoms. An early diagnosis and treatment are important for curing such patients.